APPLICATION OF GEOINFORMATICS TECHNOLOGY FOR DETECTING ACTIVE FOREST FIRES IN VIETNAM - Quang Bao, Tran; Ngoc Hoan, Le (Journal of Forestry Science and Technology, 2019)
This paper presents the results of applying geoinformatics technology in early detection of forest fires in Vietnam. Two methods were used to detect forest fires, including (1) Using ground monitoring equipment: applying algorithms to detect smoke and fire from the series of "forest fire" recorded by IP Camera, characteristics of smoke, such as color, movement and expandable properties used in fire detection; accuracy of algorithm for fire detection with video frames is 97% and with image frames from digital cameras is 100%; Ground monitoring equipment can detect 84.38% of testing fires, and indicated the cause of the fire not being detected. (2) Using MODIS satellite image: Applying algorithm developed by Louis Giglio (2003) to extract thermal anomaly from MODIS satellite image; The accuracy of using MODIS satellite image to detect forest fire from is 71% with the brightness level is from 310 degrees K and the deviation value (∆T) is 10 degrees K or more; the accuracy of forest fire detection increases by applying GIS tools and national forest inventory data to eliminate thermal anomalies outside the area of forest land. The study has proposed models to detect forest fires and transmit forest fires information from ground monitoring equipment, and from MODIS satellite images, the models can be applied for forest fire monitoring and management in Vietnam.